ANALISIS MISKONSEPSI SISWA KELAS VIII SMP GKST IMANUEL PALU BERDASARKAN CERTAINTLY OF RESPONSE INDEX (CRI) TERHADAP SOAL-SOAL MATEMATIKA: Analysis Of Students Misconception At Class VIII Smp Gkst Imanuel Palu Based On Certaintly Of Response Index About Mathematics Problem) - A. Roring, Martdelene; M., Bakri; Sugita, Gandung (Aksioma, 2023)
This research pupose to describe the misconceptions and the impacts about the pythagorean and circumference at Class VIII SMP GKST Imanuel Palu. This study used descriptive qualitative method. Data collection techniques using written tests. Checking the validity of the data with the triangulation technique method, which compares the results of tests and interviews. Data analysis consists of 3 phases, namely data reduction, data display and conclusion drawing. Based on data analysis and discussion, misconceptions occur in students which include: the pythagorean material: ((1) There is a wrong concept in planning problem solving which causes students to be unable to use the opposite Pythagorean concept (2) Students generalize the use of concepts that look the same but are different in meaning and use. In the circle material: (1). Implement the wrong circle area formula (2). Misunderstanding of concepts in the area of ​​the circle formula, (3). Misunderstanding in connecting concepts to problems. Misconceptions experienced by students are caused by: (1). the existence of associative thinking in which students associate or classify a concept is always the same as other concepts, (2). the existence of wrong intuition when planning problem solving, (3). there are students' preconceptions that are not in accordance with the operation of numbers in the Pythagorean formula.